2017
DOI: 10.1002/ajoc.201700570
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free, Visible‐Light‐Mediated Direct C−H Trifluoromethylation of Hydrazones with NADH Coenzyme Model Catalyst

Abstract: Am etal-free, visible-light-mediated directC ÀH bond trifluoromethylation of N,N-dialkylhydrazones with an NADH coenzyme modelc atalysth as been developed. The use of NADH coenzyme model makes this reaction more meaningful. Advantages of this reaction include avoidance of transition metal catalysts, high levelso ffunctional group tolerance, and mild reactionc onditions. This reaction represents am ethod to synthesize substituted hydrazones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…reported that AcrH 2 ( E * ox =−3.1 V) in the excited state was an effective reducing agent for 1 c . The reaction systems were applied to the trifluoromethylation of hydrazones 30 (Scheme b) . More recently, the Balaraman group reported the Eosin Y‐catalyzed denitronative trifluoromethylation of β‐nitoroalkenes with 1 c .…”
Section: Strategies For Reductive Generation Of Fluoromethyl Radicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that AcrH 2 ( E * ox =−3.1 V) in the excited state was an effective reducing agent for 1 c . The reaction systems were applied to the trifluoromethylation of hydrazones 30 (Scheme b) . More recently, the Balaraman group reported the Eosin Y‐catalyzed denitronative trifluoromethylation of β‐nitoroalkenes with 1 c .…”
Section: Strategies For Reductive Generation Of Fluoromethyl Radicalsmentioning
confidence: 99%
“…In 2018, Xu et al reported that AcrH 2 (E* ox = À 3.1 V) in the excited state was an effective reducing agent for 1 c. The reaction systems were applied to the trifluoromethylation of hydrazones 30 (Scheme 11b). [44] More recently, the Balaraman group reported the Eosin Y-catalyzed denitronative trifluoromethylation of βnitoroalkenes with 1 c. [45] It should be noted that Dolbier et al developed the corresponding fluorinatedmethanesulfonyl chlorides, CF 2 HSO 2 Cl and CH 2 FSO 2 Cl, [46] however, applications to organic photoredox catalysis have not yet been disclosed. In the future, development of di-and mono-fluoromethylation with these chemicals by organic photoredox catalysis is expected.…”
Section: Use Of Trifluoromethanesulfonyl Chloride (Cf 3 So 2 Cl)mentioning
confidence: 99%
“…Since visible light photoredox catalysis can provide very mild conditions for the radical formation, [11] hydrazone fluoroalkylation using iridium [12a,b] and gold [12c] metal complexes, as well as organic photocatalysts, [12d–f] was also documented. Noteworthy, certain hydrazones were reported to react with perfluoroalkyl iodides by direct photoinduced single electron transfer in the absence of any sensitizer [13] .…”
Section: Figurementioning
confidence: 99%
“…Therefore, free-radical trifluoromethylation of hydrazones has received renewed attention as an alternative for the synthesis of the corresponding C(sp 2 À H)-trifluoromethylated products. [21][22][23][24][25][26] Baud)oin, Bouyssi, Monteiro, and coworkers reported C(sp 2 À H)trifluoromethylation of the aldehyde-hydrazones (1) using the Togni's reagent (1-trifluoromethyl-1,2-benziodoxol-3(1H)-one) as the electrophilic trifluoromethylating reagent, which in the presence of the Cu(I) catalyst, generates the trifluoromethyl free radical as the reaction intermediate. [22,23] Moderate to high yields of the trifluoromethylated hydrazones 2 were obtained in this reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Xu and coworkers have used photoredox catalysis for the trifluoronethylation of hydrazones in the presence of trifluoromethanesulfonyl chloride (CF 3 SO 2 Cl) (Scheme 1). [21] However, these synthetic methods, although elegant, require the use of the potentially explosive hypervalent iodine(III) reagents (under certain conditions, especially when used in large scale synthesis) and/or expensive reagents (Togni's reagent, $99.90/g; CF 3 SO 2 Cl, $65.60/5 g). [27][28][29] Toward the goal of developing cost-effective and efficient approaches for the synthesis of the trifluoromethylated hydrazones, we now report the trifluoromethylation of the aldehyde hydrazones under mild reaction conditions, using the inexpensive, nontoxic, and bench stable Langlois reagent in the presence of Cu(II) salts as the free-radical initiators.…”
Section: Introductionmentioning
confidence: 99%